Dinâmica de uma floresta de terra firme manejada experimentalmente na região de Manaus (AM) - Pinto, Alberto Carlos Martins (Instituto Nacional de Pesquisas da Amazônia – INPA, 2008)
The present study analyzed the dynamics of a sample of “terra-firme” tropical forest, which was submitted to a selective logging in 1987 and 1988 under different felling intensity levels. The accompaniment was accomplished in permanent portions, measures before the exploration (1986) and re-measures annually starting from 1990. This study was executed in the Estação ZF-2 of INPA, the one where the project of forest handling, of the Coordination of Researches in Tropical Forestation, it was installed in 1980. Did the experiment cover an area of 72 hectares, in the form of blocks to the maybe, with 3 blocks of 24 hectares each (400 x 600 m) and 3 treatments (cut intensities) and does a witness, of 4 have each (200 x 200 m). To the whole, were 12 permanent portions of 1 analyzed there is each (100 x 100 m), done install in the center of the treatments, the one where all the arboreal individuals with DAP? 10 cm was monitored up to 2005. In the analysis of the variables (number of trees, basal area, volume and biomass), the obtained results indicate that, the remaining forest begins to answer in a positive way the application of the different cut intensities, starting from the fourth year after the selective exploration of wood (1991), starting from this moment, the statistical analyses, indicated that significant differences exist among the treatments handled for the number of trees for all the species and for the number of trees of striped commercial species (EL). With relationship the variables, basal area, volume and biomass, through the statistical analyses with repeated measures, the results indicate that, the annual average increment (ICA) and the annual medium increment (IMA) they vary significantly in the course of time, joining all the species. Through the crossing of the information of ICA's and IMA's in volume was observed that defined pattern of growth doesn't exist, being difficult to determine the ideal moment for application of the treatments of forest trees, that suggest rough-hewing. Using the chain of transition of Markov, to do projections on the number of trees projected in comparison with the number of trees observed in the period, they show that the treatments T2 and T3 in each diameter class presented the best results. The dynamics of the handled forest was more favored for the new individuals' entrance than for the mortality, mainly in the period of 1999-2002, where T2 presented the best acting, in other words, the forest handling used in that study it was it of the natural regeneration, that it proposes the maintainable use of the wood production, without the application of treatments of the trees. In spite of that, all the treatments had starting from the fourth year after the exploration, growth in basal area, volume and biomass in the course of time. Indicating that the handled forest, in a more optimistic estimate, it can recover the original volume of the first extraction, in one period of approximately 12 years, in other words, after 30 years of the first exploration. Besides, the applied forest handling in that area provided the emergence of other species in the study area, mainly in the treatment T1 and T3 and the diversity of species was considered highly significant in the course of time. In other words, the selective exploration of wood provided changes in the composition of the trees, but, it didn't provoke the decrease in the wealth of species after your application.
Keywords: Manejo florestal; Exploração florestal; Cadeia de Markov